2015
DOI: 10.7554/elife.11352
|View full text |Cite
|
Sign up to set email alerts
|

Sexually divergent expression of active and passive conditioned fear responses in rats

Abstract: Traditional rodent models of Pavlovian fear conditioning assess the strength of learning by quantifying freezing responses. However, sole reliance on this measure includes the de facto assumption that any locomotor activity reflects an absence of fear. Consequently, alternative expressions of associative learning are rarely considered. Here we identify a novel, active fear response (‘darting’) that occurs primarily in female rats. In females, darting exhibits the characteristics of a learned fear behavior, app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
308
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(382 citation statements)
references
References 24 publications
(24 reference statements)
44
308
6
Order By: Relevance
“…However, failure of training to correlate with extinction in SEFL females introduces the possibility they are expressing their response to foot shock through non-freezing behaviors. For instance, darting is described as a coping mechanism that correlates with extinction retention in female rats (67). Alternatively, females could be displaying active avoidance/escape behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…However, failure of training to correlate with extinction in SEFL females introduces the possibility they are expressing their response to foot shock through non-freezing behaviors. For instance, darting is described as a coping mechanism that correlates with extinction retention in female rats (67). Alternatively, females could be displaying active avoidance/escape behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The answer to this question may lie with evidence that female and male rodents exhibit different behavioral repertoires when presented with a threat. Several studies have shown that females show superior performance when active responses are measured whether it be classical eyeblink conditioning (Wood and Shors 1998;), fear conditioning (Gruene et al 2015b), or avoidance tasks (Steenbergen et al 1990;Dalla et al 2008). Thus, it is possible that the tendency for females to engage in more active fear responses obscures reliable sex differences in conditioning and/or extinction when freezing behavior is the only measure.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of freezing behavior, differences in activity levels between males and females might complicate the interpretation of experiments which use inactivity as an index of fear. This issue is highlighted by a recent observation that female rats exhibit an active conditioned fear response (i.e., darting) that is not frequently seen in males (Gruene et al 2015b). To further characterize the effect of sex on measures of fear conditioning and extinction, in the current study we compared levels of fear conditioning and extinction in males and females using both freezing behavior and fearpotentiated startle as measures.…”
mentioning
confidence: 97%
“…It should be noted that, when considering fear as expressed by freezing, these studies have been restricted to males. Recent studies indicate that females employ active avoidance responses and males shift to these when the size of the chamber is increased (Gruene et al, 2015).…”
Section: Emotional Contagion: Social Modulation Of Fear and Painmentioning
confidence: 99%